Shear Properties and Mechanism of Freeze-Thaw Interface in Unsaturated Coarse-Grained Soil from Qinghai-Tibet Plateau - Yonglong Qu; Wankui Ni; Fujun Niu; Yanhu Mu; Jing Luo; Hui He (Advances in Civil Engineering)
Freeze-thaw interface in unsaturated coarse-grained soil (CGS) is a weak plane which can cause slope failures in cold regions. This study presents a series of large-scale direct shear tests on freeze-thaw interface in CGS through a temperature control system. The tested soil was taken from a high slope in the Qinghai-Tibet Plateau. It was remolded with three dry densities (1.9, 2.0, and 2.15 g/cm3) and three moisture contents (9.0%, 11.5%, and 14.0%). With testing results, direct shear curves mainly performed as hardening deformation, and they were affected considerably by specimen conditions. The shear strength increased with both the increasing dry density and normal stress, but it was opposite with moisture content changed. The cohesion and internal friction angle increased with the increase in dry density but decreased with the moisture content. The particle movement and water migration of freeze-thaw interface in CGS during the test were significant, and they had close relations with the shear properties of specimens. And, an empirical model was produced to express the effect of pore ice on the shear strength of interface during the shear test. The tests and analysis in this study may provide useful references for CGS slope stability analysis in high cold regions.